1984
DOI: 10.3171/jns.1984.60.6.1167
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled double-blind trial of nimodipine after SAH in monkeys

Abstract: The authors have developed a method to induce chronic cerebral vasospasm after subarachnoid hemorrhage (SAH) in monkeys. With microsurgical techniques, 33 monkeys had a frontotemporal craniectomy and unilateral opening of the subarachnoid cisterns. Cerebrospinal fluid was drained and a fresh hematoma, obtained from an average of 7 ml of autologous blood, was carefully placed against the major arteries of the anterior circulation on one side. The 30 monkeys studied for 7 to 14 days after the SAH were allocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(47 citation statements)
references
References 15 publications
(2 reference statements)
0
47
0
Order By: Relevance
“…An additional 64 studies were excluded after reading the full text because they did not completely fulfill the inclusion criteria or they reported preliminary or incomplete data. Data from 70 papers were then extracted (Bilginer et al, 2009;Bulsara et al, 2006;Caner et al, 1996;Chang et al, 2010;Chen et al, 2009;Cheng et al, 2009;Chung and Lee, 1993;Cosentino et al, 1993;Espinosa et al, 1984;Findlay et al, 1988Findlay et al, , 1989Findlay et al, , 1990Grasso et al, 2002;Gul et al, 2010;Hanggi et al, 2009;Hariton et al, 1993;Hino et al, 1995;Itoh et al, 1993Itoh et al, , 1994Josko et al, 2000;Kanamaru et al, 1990Kanamaru et al, , 1991Kawada et al, 1999;Kawashima et al, 2000;Kim et al, 1996Kim et al, , 2000Kita et al, 1998;Kwan et al, 1997Kwan et al, , 2001Kwan et al, , 2006Laslo et al, 2006;Lewis et al, 1988;Lin et al, 2007;Macdonald et al, 1998aMacdonald et al, , b, 2004Marbacher et al, 2008;Matsui and Asano, 1994;Matsumura et al, 1991;McGirt et al, 2002McGirt et al, , 2006…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 64 studies were excluded after reading the full text because they did not completely fulfill the inclusion criteria or they reported preliminary or incomplete data. Data from 70 papers were then extracted (Bilginer et al, 2009;Bulsara et al, 2006;Caner et al, 1996;Chang et al, 2010;Chen et al, 2009;Cheng et al, 2009;Chung and Lee, 1993;Cosentino et al, 1993;Espinosa et al, 1984;Findlay et al, 1988Findlay et al, , 1989Findlay et al, , 1990Grasso et al, 2002;Gul et al, 2010;Hanggi et al, 2009;Hariton et al, 1993;Hino et al, 1995;Itoh et al, 1993Itoh et al, , 1994Josko et al, 2000;Kanamaru et al, 1990Kanamaru et al, , 1991Kawada et al, 1999;Kawashima et al, 2000;Kim et al, 1996Kim et al, , 2000Kita et al, 1998;Kwan et al, 1997Kwan et al, , 2001Kwan et al, , 2006Laslo et al, 2006;Lewis et al, 1988;Lin et al, 2007;Macdonald et al, 1998aMacdonald et al, , b, 2004Marbacher et al, 2008;Matsui and Asano, 1994;Matsumura et al, 1991;McGirt et al, 2002McGirt et al, , 2006…”
Section: Resultsmentioning
confidence: 99%
“…Investigators used monkeys (Macaca species), dogs (mongrel or beagles), rabbits (Japanese or New Zealand species), rats (Sprague Dawley or Wistar species) and mice ( Espinosa et al (1984); Findlay et al (1988Findlay et al ( , 1989Findlay et al ( , 1990; Hariton et al (1993); Hino et al (1995); Kanamaru et al (1990Kanamaru et al ( , 1991; Kim et al (1996); Lewis et al (1988); Macdonald et al (2004); Nosko et al (1985); Steinke et al (1989); Suzuki et al (1998Suzuki et al ( , 1999 Wanebo et al (1997Wanebo et al ( , 1998; Zuccarello et al (1989Zuccarello et al ( , 1996Zuccarello et al ( , 1998 Method of induction of SAH Clot placement 17 (23) Espinosa et al (1984); Findlay et al (1988Findlay et al ( , 1989Findlay et al ( , 1990; Hariton et al (1993); Hino et al (1995); Kanamaru et al (1990Kanamaru et al ( , 1991Kanamaru et al ( , 2000; Kim et al (1996); Lewis et al ( Kanamaru et al (1990Kanamaru et al ( , 1991; Kawada et al (1999); Kawashima et al (2000); Kim et al (1996Kim et al ( , 2000; Kita et al (1998); Kwan et al (1997Kwan et al ( , 2001Kwan et al ( , 2006 Wanebo et al (1997<...>…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…However, the effect is very modest, preventing bad outcome in only one of 13 treated patients (Feigin et al, 1998). Nimodipine does not affect angiographic vasospasm at the clinically used dose (Allen et al, 1983;Espinosa et al, 1984), suggesting that clinical effects are due to either direct neuroprotection or other factors, such as prevention of spreading ischemia (see below). In contrast, one of the experimental treatments tried against delayed cerebral ischemia in SAH, the endothelin receptor antagonist clazosentan, reduced angiographic vasospasm, but had no significant effect on long-term clinical outcome (Macdonald et al, 2008a).…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…7,20,23,26) Animal studies show that vasospasm identical to that occurring in humans can be reproduced by placing autologous blood clots next to the cerebral arteries or by injection of adequate amounts of blood into the cerebrospinal fluid (CSF). 4,17,19) The Fisher classification system, which evaluates the amount of blood in the cisterns and the ventricles by CT, is widely recognized to identify patients at high risk for the development of DIND. 7) The present study found that angiographical vasospasm did not appear in the arteries in cisterns with thick clots, where vasospasm is most likely, but occurred in arteries remote from the site of NPRI pellet placement.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there have been many reports of intrathecal fibrinolytic therapy. We also have reported the continuous cisternal irrigation of urokinase and ascorbic acid, 3,4) but it is undeniable that the procedure is complicated and some procedure-related complications exist. Considering these points, this method seems to be promising.…”
Section: Commentarymentioning
confidence: 99%